Transcatheter Valve-in-Valve Procedures for Bioprosthetic Valve Dysfunction in Patients With Rheumatic vs. Non-Rheumatic Valvular Heart Disease - Lopes, Mariana Pezzute; Rosa, Vitor Emer Egypto; Palma, José Honório; Vieira, Marcelo Luiz Campos; Fernandes, Joao Ricardo Cordeiro; de Santis, Antonio; Spina, Guilherme Sobreira; Fonseca, Rafael de Jesus; de Sá Marchi, Mauricio F.; Abizaid, Alexandre; de Brito, Fábio Sândoli; Tarasoutchi, Flavio; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Bioprosthetic heart valve has limited durability and lower long-term performance especially in rheumatic heart disease (RHD) patients that are often subject to multiple redo operations. Minimally invasive procedures, such as transcatheter valve-in-valve (ViV) implantation, may offer an attractive alternative, although data is lacking. The aim of this study was to evaluate the baseline characteristics and clinical outcomes in rheumatic versus non-rheumatic patients undergoing ViV procedures for severe bioprosthetic valve dysfunction. Methods: Single center, prospective study, including consecutive patients undergoing transcatheter ViV implantation in aortic, mitral and tricuspid position, from May 2015 to September 2020. RHD was defined according to clinical history, previous echocardiographic and surgical findings. Results: Among 106 patients included, 69 had rheumatic etiology and 37 were non-rheumatic. Rheumatic patients had higher incidence of female sex (73.9% vs 43.2%, respectively; p=0.004), atrial fibrillation (82.6% vs 45.9%, respectively; p<0.001), and 2 or more prior surgeries (68.1% versus 32.4%, respectively; p=0.001). Although, device success was similar between groups (75.4% versus 89.2% in rheumatic versus non-rheumatic, respectively; p=0.148), there was a trend towards higher 30-day mortality rates in the rheumatic patients (21.7% vs 5.4%, respectively; p=0.057). Still, at median follow-up of 20.7 [5.1 – 30.4] months, cumulative mortality was similar between both groups (p=0.779). Conclusion: Transcatheter ViV implantation is an acceptable alternative to redo operations in the treatment of patients with RHD and severe bioprosthetic valve dysfunction. Despite similar device success rates, rheumatic patients present higher 30-day mortality rates with good mid-term clinical outcomes. Future studies with a larger number of patients and follow-up are still warranted, to firmly conclude on the role transcatheter ViV procedures in the RHD population.